2021
DOI: 10.1002/joa3.12557
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six risk scores for the prediction of atrial fibrillation recurrence after cryoballoon‐based ablation and development of a simplified method, the 0‐1‐2 PL score

Abstract: Introduction There are several prognostic scores for the assessment of risk of atrial fibrillation (AF) recurrence post ablation procedure. However, the use of these complex scores is difficult and the validation on different populations brought divergent results. Our goal was to compare the performance of these risk scores as the basis for the development of a new, simplified score based only on few universally predictive variables. Methods All cryoballoon‐based AF ablations performed in a single‐center over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Our results are consistent with the two recent studies comparing AF recurrence risk prediction scores, which also showed only modest predictive value for all scores [13,14]. This underscores the ongoing challenge of predicting AF recurrence after AF ablation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with the two recent studies comparing AF recurrence risk prediction scores, which also showed only modest predictive value for all scores [13,14]. This underscores the ongoing challenge of predicting AF recurrence after AF ablation.…”
Section: Discussionsupporting
confidence: 92%
“…Several predictive scores for AF recurrence after ablation have been developed. The predictive value of such scores has thus far been limited [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the BASE-AF2 score was designed to assess recurrence of AF at extended follow-up after CBA. In addition, a recent study by Jastrzebski and colleagues evaluated the efficacy of various risk scores in predicting recurrence of AF over 10 years after ablation [ 21 ]. In their cohort of 617 consecutive patients who underwent catheter ablation, SCALE-CryoAF predicted recurrent AF over 10 years post ablation better than APPLE, CAAP-AF, CHADS 2 , CHA 2 DS 2 -VASc, and MB-LATER [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study by Jastrzebski and colleagues evaluated the efficacy of various risk scores in predicting recurrence of AF over 10 years after ablation [ 21 ]. In their cohort of 617 consecutive patients who underwent catheter ablation, SCALE-CryoAF predicted recurrent AF over 10 years post ablation better than APPLE, CAAP-AF, CHADS 2 , CHA 2 DS 2 -VASc, and MB-LATER [ 21 ]. However, neither of the aforementioned studies specifically evaluated for VLRAF after CBA and instead included patients with recurrent AF within one year after ablation in their analyses.…”
Section: Discussionmentioning
confidence: 99%